Analisis Kualitas Hasil Produksi Kawat Baja Single Wire di PT. XYZ dengan Menggunakan Metode FMEA - Arnanda Ahmad Ar Ridlo; Efta Dhartikasari Priyana; Yanuar Pandu Negoro (Jurnal Serambi Engineering, 2023)
PT XYZ is a steel wire specialist company engaged in manufacturing. PT. XYZ also makes quality the company's quality so that it will have a competitive advantage against competitors in the world market, because not all companies are able to make quality a superior strategy to compete. Therefore, companies are required to produce products with good quality. But in reality, the production field experienced various problems during the work process which resulted in defective products in the production process which were not good and raised question marks. This study aims to use the FMEA (Failure Mode and Effect Analysis) method in order to reduce product defects. In this study, an assessment was carried out with the calculation results in the form of an RPN (Risk Priority Number) value by filling out a questionnaire. In this method there are several tools used to help solve problems, namely pareto charts, fishbone diagrams,and flowcharts. In order to obtain data acquisition of 13 indicators of product defects at PT XYZ. The results showed that the highest risk of defects in corrugated wire products was loose roll bolts with an RPN value of 240, over diameters were deformed/rough dies with an RPN value of 336, and scratched wire was deformed/rough dies with an RPN value of 392.